Penerapan Model Pembelajaran Generatif Pada Materi Usaha dan Pesawat Sederhana Kelas VIII MTs Nurussalam Sidogede OKU Timur - Effendi Effendi; Dwi Pantriani (Physics Education Research Journal, 2020)
The purpose of this study was to determine the effect of the application of Generative learning models on student learning outcomes in the Work and Simple Machine in MTs Nurussalam Sidogede grade VIII. The type of this research is a quantitative research. The population in this research were students of class VIII at MTS Nurussalam Sidogede consisting of 4 classes. Sampling in this study was randomly drawn. The experimental class uses the generative learning model, while the control class uses the conventional learning model. Data collection techniques using tests, and testing of hypotheses using t-test. Based on student learning outcomes obtained tcount = 3.09 which is more than ttable = 2.01; so it can be concluded that there are significant differences in learning outcomes between students with generative learning models and students with conventional learning models.